Development of biochar from oil palm frond for palm oil mill effluent treatment - Abdullahi, Lawal Abubakar (2021)
In order to meet the growing demand for adsorbents to treat wastewater effectively, there has been increased interest in producing biochar from sustainable biomass feedstocks at minimum energy input. Although physical and chemical activations have been commonly employed to produce activated biochar with superior textural properties capable of treating wastewater effectively, little attention has been given to the effect of biomass nature and pyrolysis agents on biochar structure and adsorption performance. Therefore, the purpose of this research is to evaluate the effect of biomass cellulosic content and steam pyrolysis on evolution of pyrogenic nanopores and molecular structures of biochar, and evaluates the performance of biochar from oil palm frond (OPF) with respect to treating POME final discharge. Commercial cellulose, OPF, and palm kernel shell were pyrolyzed at 630 °C, and their biochar structures were analyzed. Evaluation of biochar nanotexture based on cellulosic content revealed that commercial cellulose decomposed rapidly into non-graphitizing large size crystallites (65 nm) with substantial defects within their graphene sheets forming mesopores resulting in the external surface area (SAext) of 95.4 m2 /g and micropore surface area (SAmi) of 231.2 m2 /g. Amorphous chars derived from lignin were thermally stable, slowing down the rapid formation of crystallites in biochar from palm kernel shell, which resulted to forming microporous structure with SAmi of 377.0 m2 /g and SAext of 58.6 m2 /g. Biochar from OPF had SAmi of 293.4 m2 /g and SAext of 73.3 m2 /g. The iodine number of the biochars from commercial cellulose, OPF and palm kernel shell correlated with the SAext demonstrating the suitability of mesoporous biochar for wastewater treatment. Increasing the pyrolysis temperature from 400 to 600 °C in presence of superheated steam increased the BET surface area (SABET) of biochar from OPF from 1.63 to 461.3 m2 /g, while increasing retention time from 2 to 10 h at 600 °C increased the SABET from 461.3 to 530.1 m2 /g. Comparatively, steam pyrolysis of OPF at 600 °C produced biochar with higher SABET of 461.3 m2 /g and SAext of 189.4 m2 /g compared to nitrogen pyrolysis with lower SABET of 368.4 m2 /g and SAex of 77.4 m2 /g demonstrating pore broadening activity of steam. Steam pyrolyzed biochar from OPF achieved a maximum adsorption capacity of 24.6 mg/g COD, 49 mg/g Pt-Co, 58.1 mg/g phenol, and 63.6 mg/g tannic acid by interacting with the contaminants through van der Waals force, π-π interactions, H bonding, and water-bridged H bonding. Using 30 g/L dosage, the biochar from OPF exhibited an effective reduction of COD from 224 to 41.6 mg/g and color from 344 to 15 Pt-Co. Findings of this work revealed the tendency of cellulose to yield a mesoporous biochar and demonstrated the effectiveness of steam pyrolysis in terms yielding biochar with superior textural properties through its greater pore deepening and broadening activities. Biochar from OPF was capable of engaging into multiple adsorption mechanisms signifying its high affinity for a variety of organic contaminants and suitability for wastewater treatment.